The Potential of Cytotoxin and Antiviral in Sargassum polycystum and Sargassum ilicifolium’s Polysaccharides Extract - Dwi Lestari Widya Ningsih; Agus Trianto; Ita Widowati; Rexie Magdugo; Anicia Hurtado; Christel Marty; Nathalie Bourgougnon (Marine Science Department Diponegoro University, 2020)
Marine algae known as one producers of bioactive compounds. This study aims to analyze the cytotoxicity and antiviral activity in Sargassum polycystum and Sargassum ilicifolium tested with Herpes Simplex Virus (HSV). The polysaccharides extract of algae was used in this study, as sulfated polysaccharides have been reported has bioactivity. Cytotoxicity either antiviral could be correlated with the sulfate content as well as nature and chemical composition of the polysaccharides. Cytotoxicity and antiviral analysis based upon cell viability. Using the Vero cell / HSV-1 model, cytotoxicity was evaluated by incubating cellular suspensions (3.5×105 cells.mL-1) with various dilutions (concentration from 1 to 500 µg.mL-1, four wells per concentration) of fractions in 96-well plates (72h, 37°C, 5% CO2) in Eagle's MEM containing 8% FCS. The cells were examined daily under a phase-contrast microscope to determine the minimum concentration of hydrolysate dry matter that induced alterations in cell morphology, including swelling, shrinkage, granularity and detachment. Algae S. illicifolium was found to have the highest cytotoxic content in each solution compared to S. polycystum. Algae S. illicifolium in KOH 4M (cellulose) reached 2,707 µg.ml-1, then HCl pH 2 (fucoidan) was 2,477 µg.ml-1, then CaCl2 2% (fucoidan) was 2,362 µg.ml-1, and in Na2CO3 3% (alginates) was 2,134 µg.ml-1. For antiviral, S. polycystum contained the highest antiviral compounds compared to S. illicifolium with KOH 4M (cellulose) solution was reached 67.02 µg.ml-1. Then in Na2CO3 3% (alginates) which was 33.25 µg.ml-1, then CaCl2 2% (fucoidan) which was 31.62 µg.ml-1,and HCl pH 2 (fucoidan) was 30.08 µg.ml-1. After all, the highest bioactivity compounds was found with KOH 4M (cellulose) for cytotoxicity in S. ilicifolium and antiviral activity in S. polycystum.